Экспрессивная функция префиксальной морфемы в романе А.С. Пушкина - Горбунова, Светлана (Studia Rossica Posnaniensia, 2014)
The article is devoted to studying word-building as a means of achieving expression in Pushkin’s Eugene Onegin; particular attention is given to the prefixal morpheme. As for the fact that the novel was written in verse, the author analyzes the processes associated with implementing the poetic function of language